1995
DOI: 10.1152/ajpgi.1995.269.4.g512
|View full text |Cite
|
Sign up to set email alerts
|

Effect of short-term starvation on gastric emptying in humans: relationship to oral glucose tolerance

Abstract: To evaluate the effects of short-term starvation on gastric emptying in normal and obese subjects, the relationship between gastric emptying and oral glucose tolerance, and the mechanisms responsible for the delay in the systemic appearance of oral glucose observed after short-term fasting, we determined the effects of a 4-day fast on 1) gastric emptying and oral glucose tolerance in normal subjects and 2) gastric emptying in obese patients. Gastric emptying of 75 g glucose (320 ml) labeled with 99mTc colloid … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
52
0

Year Published

1998
1998
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(54 citation statements)
references
References 0 publications
2
52
0
Order By: Relevance
“…For example, the effects of fat on gastric emptying and oro-cecal transit are attenuated following consumption of a high-fat diet so that, in healthy males, consumption of a high-fat, hypercaloric diet for 14 days is associated with marked acceleration of GE and mouth-to-cecum transit of a high-fat, solid test meal when compared with a low-fat diet (14). Moreover, in healthy young (15) and older (2) subjects, short-term glucose supplementation accelerates GE of a glucose drink, whereas fasting slows GE (10). That there were no differences in habitual fat or energy intake between the lean, overweight, and obese groups in our study is not surprising given that all subjects were weight-stable, and this could well account for the absence of any difference in GE between the groups.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the effects of fat on gastric emptying and oro-cecal transit are attenuated following consumption of a high-fat diet so that, in healthy males, consumption of a high-fat, hypercaloric diet for 14 days is associated with marked acceleration of GE and mouth-to-cecum transit of a high-fat, solid test meal when compared with a low-fat diet (14). Moreover, in healthy young (15) and older (2) subjects, short-term glucose supplementation accelerates GE of a glucose drink, whereas fasting slows GE (10). That there were no differences in habitual fat or energy intake between the lean, overweight, and obese groups in our study is not surprising given that all subjects were weight-stable, and this could well account for the absence of any difference in GE between the groups.…”
Section: Discussionmentioning
confidence: 99%
“…Finally it should be noted that, in all of these studies, re-examination took place immediately after termination of the weight-reducing diet-intervention, and it is therefore impossible to distinguish between effects of the reduced weight and the possible effects of negative energy balance per se. 44,45 Recently, Teff et al have shown that increased activity in the parasympathetic efferent simulation of the stomach might be the mechanism that leads to an increased gastric emptying in obese subjects. 29 Another theory is that a higher initial emptying rate in obese individuals is caused by an adaptation to a high energy intake, or a high fat energy percentage.…”
Section: Discussionmentioning
confidence: 99%
“…The outcome of gut hormone measurements is also inconsistent, for example, some studies have reported lower fasting ghrelin, 15 higher fasting 18 and postprandial 16 plasma CCK, and lower postprandial PYY, 19 glucagon-like peptide-1 20 and ghrelin 21 concentrations, whereas others found no differences in PYY or glucagon-like peptide-1. 15 There is evidence that previous patterns of energy intake, in excess, in restriction and even when sustained for short periods of time, have the capacity to modify gastrointestinal function, 5,[22][23][24] and this may be of particular relevance to the inconsistent observations from studies relating to gastrointestinal function in the obese given that previous nutrient intake has not been quantified. For example, in healthy subjects, a 2-week period on a high-fat diet accelerates gastric emptying of a high-fat meal.…”
Section: Introductionmentioning
confidence: 99%
“…5 In contrast, fasting appears to have the opposite effect, so that after a 4-day fast, gastric emptying of glucose is slower in both lean and obese subjects. 22 The nutrient deprivation of critical illness is associated with delayed gastric emptying and increased plasma CCK and PYY concentrations, 23 with evidence that increased small-intestinal feedback contributes to the slowing of gastric emptying. 24 We have now evaluated, in obese subjects, the effects of short-term energy restriction on antropyloroduodenal (APD) motility, plasma CCK, PYY and ghrelin concentrations, and appetite and energy intake, in response to administration of intraduodenal lipid.…”
Section: Introductionmentioning
confidence: 99%